Analisis Akad Pinjaman Sosial di Koperasi Serba Usaha (KSU) Desa Kota Indonesia dalam Perspektif Hukum Ekonomi Syari’ah - Awala Mahromia; Aminulloh, Ali; Prawoto, Imam; Samsudin, Agus Rojak (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2025)
Social loans are an important tool for developing local economies, especially in remote areas such as rural areas. The Indonesian Village City Savings and Loan Cooperative (KSU) is one of the business entities that provides loan capital to its members. The purpose of this study is to determine the mechanism of social loan agreements in the Multipurpose Cooperative (KSU) of the Indonesian Village City and to determine the perspective of Islamic Economic Law on loan agreements in the Multipurpose Cooperative (KSU) of the Indonesian Village City. This research method uses a descriptive research type with a qualitative approach. Data collection was carried out through observation and interviews with the Management and members of the Savings and Loan Cooperative (KSU) of the Indonesian City Village. The results of the study show that first, the loan application procedure involves several steps such as becoming a member, filling out forms, completing documents and the approval stage. The maximum loan provision is 80% of the savings balance with a loan tenor of 12 months and 18 months. The payment system is made in installments through salary deductions and is subject to a 5% interest. For borrowing members who are late, there are no sanctions or fines but there is a time dispensation. Second, the loan application and management mechanism at the Multipurpose Cooperative has met sharia principles through transparent and structured governance, such as deductions from salary installments and a guarantee policy provided in the form of the amount of member savings balances. However, social loans at the Multipurpose Cooperative contain an element of benefit (profit) of 5%, which according to some scholars can be classified as usury because of the addition of value to the principal loan, even though the benefit is returned to members through the Business Result Remainder (SHU).